Faktor-Faktor yang Mempengaruhi Intensi Petani Ternate dalam Melakukan Pertanian Organik - Fuady, Ikhsan; Mardianah, Mardianah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Organic farming is one alternative farming system that is environmentally friendly and sustainable. Various kinds of activities to accelerate the development of organic agriculture in the city of Ternate have been carried out, but the productivity of organic agriculture is still relatively low. Many factors affect the intention of farmers to conduct organic farming. This study aims to determine the factors that influence the intention of farmers to carry out organic farming, within the framework of the technology acceptance model (TAM) theory. The research method used is the quantitative method of the survey approach. The study population was members of farmer groups in Ternate. The sampling technique used is multistage cluster random sampling. The sample of this research were 46 farmers. The results showed that the intention of farmers to carry out organic farming 65.5 percent of high-categorized farmers. In its agricultural business, farmers have started to utilize environmentally friendly agricultural inputs such as compost, and also plant-based pesticides. Most farmers have been able to independently make organic fertilizers such as location fertilizer with MOL independently. For factors that influence farmers to do organic farming, among others, are farmers' perceptions of the benefits of organic farming, with a correlation coefficient of 0.845 and a significance of 0.007. Another factor influencing farmers' intention to do organic farming is risk perception with a correlation coefficient of 0.296 and a significance value of 0.000. Benefit perception refers to the farmer's view of how much benefit is gained by carrying out an organic farming system. While risk perception refers to the small risk obtained by conducting an organic farming system.